2020
DOI: 10.1038/s42005-019-0271-0
|View full text |Cite
|
Sign up to set email alerts
|

Time-delay polaritonics

Abstract: Non-linearity and finite signal propagation speeds are omnipresent in nature, technologies, and real-world problems, where efficient ways of describing and predicting the effects of these elements are in high demand. Advances in engineering condensed matter systems, such as lattices of trapped condensates, have enabled studies on non-linear effects in manybody systems where exchange of particles between lattice nodes is effectively instantaneous. Here, we demonstrate a regime of macroscopic matter-wave systems… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 54 publications
5
60
0
Order By: Relevance
“…In all proposed schemes the nearest neighbour interactions are attempted to be controlled while the beyond nearest neighbour interactions are assumed to be negligible, which is rarely the case. A recent study has shown the synchonisation between condensates across distances over 100 µm [45] noting that a typical lattice size constant is often in the range of 5-15 µm [40]. This leads to a crucial and yet missing discussion of controlling the couplings beyond nearest neighbours for arbitrary graphs of polariton condensates.…”
Section: Introductionmentioning
confidence: 99%
“…In all proposed schemes the nearest neighbour interactions are attempted to be controlled while the beyond nearest neighbour interactions are assumed to be negligible, which is rarely the case. A recent study has shown the synchonisation between condensates across distances over 100 µm [45] noting that a typical lattice size constant is often in the range of 5-15 µm [40]. This leads to a crucial and yet missing discussion of controlling the couplings beyond nearest neighbours for arbitrary graphs of polariton condensates.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their non-equilibrium nature, polaritons can diffuse away from their pumping spots, transforming their potential energy into kinetic energy. Such a flow of coherent polaritons [23][24][25], with tunable cavity in-plane momentum, then leads to interference and robust phase locking between spatially separated condensates [26][27][28][29][30].…”
mentioning
confidence: 99%
“…For physical implementation of our scheme, exciton polaritons in planar microcavities have shown to form interconnected networks [28][29][30][31] and also to reach the quantum nonlinear regime [23,32]. It can also be implemented in other systems, like arrays of quantum dots, trapped ions and atoms, nonlinear optical cavities, and networks of superconducting qubits where classical optical sources can interact with quantum nonlinear systems to generate quantized output fields.…”
mentioning
confidence: 99%